EVALUATION OF MAP COLLECTIONS AND CARTOGRAPHIC INFORMATION NEEDS OF SPECIAL AND ACADEMIC LIBRARIES IN SRI LANKA - PERERA, P.K. (a degree of Master of Library and Information Science, 2004)
Although map collections have a long and evolutionary history, the profession of map librarianship has not yet established in Sri Lanka. Developments in new technology have radically changed the nature of map production and the distribution of spatial data among users. This study was designed to identify collection of maps (map collection) in libraries of Sri Lanka and to evaluate the cartographic information needs of users in special libraries and academic libraries. To identify libraries and institutions, that use maps, a prebrminary survey was conducted. 35 special libraries and 8 university libraries were identified. A survey was then carried out to identify the users of maps in these institutions and universities. It was found that the number of users was limited. Therefore the whole population was taken into the survey. Two sets of questionnaires were sent to the libraries/ institutions and to the users respectively. With the results of this study, it was possible to identify maps according to four main categories, namely special libraries, map centres in institutions, map libraries in universities and geography and geology departments in universities. Nine (9) map producing institutions were also identified along with the Survey Department of Sri Lanka. Map collections in the above four categories were analyzed under type and format of maps, organization, storage, collection management and user services.